2021
DOI: 10.3389/fonc.2021.682021
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals MFGE8-HAPLN3 Fusion as a Novel Biomarker in Triple-Negative Breast Cancer

Abstract: BackgroundTriple-negative breast cancer (TNBC) is a highly aggressive cancer with poor prognosis. The lack of effective targeted therapies for TNBC remains a profound clinical challenge. Fusion transcripts play critical roles in carcinogenesis and serve as valuable diagnostic and therapeutic targets in cancer. The present study aimed to identify novel fusion transcripts in TNBC.MethodsWe analyzed the RNA sequencing data of 360 TNBC samples to identify and filter fusion candidates through SOAPfuse and ChimeraSc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…sEVs are important players in intercellular communication and are implicated in tumorigenesis and metastasis [ 8 11 , 13 , 14 , 16 ]. On the other hand, lactadherin overexpression has been associated with poor prognosis in several types of cancers, including BC [ 60 62 ]⁠. Thus, we evaluated the presence of this protein in BC cell-secreted sEVs obtained from MCF7, T47D, and MDA-MB-231 BC cell supernatants using ultracentrifugation (sEV-MCF7, sEV-T47D, and sEV-MDA231).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…sEVs are important players in intercellular communication and are implicated in tumorigenesis and metastasis [ 8 11 , 13 , 14 , 16 ]. On the other hand, lactadherin overexpression has been associated with poor prognosis in several types of cancers, including BC [ 60 62 ]⁠. Thus, we evaluated the presence of this protein in BC cell-secreted sEVs obtained from MCF7, T47D, and MDA-MB-231 BC cell supernatants using ultracentrifugation (sEV-MCF7, sEV-T47D, and sEV-MDA231).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that lactadherin is associated with poor prognosis and bad outcomes in several types of cancer [ 43 , 60 62 ]. However, little is known about the role and importance of its presence in sEVs, and whether it can influence sEV-mediated tumorigenic and/or pro-metastatic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Hapln3/LP3 is widely expressed, mainly outside the brain (Spicer et al, 2003). It was reported to be involved in breast, kidney and prostate cancer (Strand et al, 2014;Wang et al, 2021;Ding et al, 2023) but its role in brain ischemia has not yet been investigated.…”
Section: Ecm Molecules In Perineuronal Netsmentioning
confidence: 99%
“…This gene fusion was much more frequent in TNBC than in other subtypes. The authors further validated the presence of the MFGE8–HPLN3 gene fusion in TNBC biopsies, and predicted the length of the encoded protein, suggesting its critical role in TNBC biology, and a possible clinical application as a new biomarker [ 47 ]. In Table 1 , we listed the main discoveries of lactadherin research regarding cancer development and its importance as a biomarker of this disease.…”
Section: Lactadherin As a Biomarker Of Tumor Subtype Progression And ...mentioning
confidence: 99%